Comparison of gas chromatography-mass spectrometry and gas chromatography-tandem mass spectrometry with electron ionization for determination of N-nitrosamines in environmental water. (February 2017) - Chen, Wenwen; Li, Xiaoshui; Huang, Huanfang; Zhu, Xuetao; Jiang, Xiaoyu; Zhang, Yuan; Cen, Kuang; Zhao, Lunshan; Liu, Xiuli; Qi, Shihua
Abstract: N -nitrosamines are trace organic contaminants of environmental concern when present in groundwater and river water due to their potent carcinogenicity. Therefore, N -nitrosamine analysis is increasingly in demand. Gas chromatography-mass spectrometry (GC-MS) and GC-tandem mass spectrometry (GC-MS/MS), both with electron ionization (EI), were compared for analysis of nine N -nitrosamines extracted from environmental water matrices. A total of 20 fishpond water, river water, and groundwater samples from Sihui and Shunde, China were collected for a survey of N -nitrosamine concentrations in real water samples. Various solid-phase extraction (SPE) conditions and GC conditions were first examined for the pre-concentration and separation steps. The analysis of N -nitrosamines in environmental waters demonstrated that their quantification with GC-MS poses a challenge due to the occurrence of co-eluting interferences. Conversely, the use of GC-MS/MS increased selectivity because of the fragmentation generated from precursor ions in the 'multiple reaction monitoring' (MRM) mode, which is expected to extract target analytes from the environmental water matrix. Thus, the high performance of GC-MS/MS with EI was used to quantify nine N -nitrosamines in environmental waters with detection limits of 1.1–3.1 ng L −1 . N -nitrosodimethylamine (NDMA) concentrations were in the range of N.D. to 258 ng L −1 . Furthermore, other N -nitrosamines, except N -nitrosomethylethylamine (NMEA), N -nitroso-di- n -propylamine (NDPA) and N -nitrosopiperidine (NPIP), were also detected. Our findings suggest that GC-MS/MS with EI would be widely applicable in identifying N -nitrosamines in environmental waters and can be used for routine monitoring of these chemicals. Highlights: Systemic comparison on N -nitrosamine analysis in water using GC-MS and GC-MS/MS-EI. Environmental water samples were analyzed to characterize the influence of the water matrix. Miscellaneous adverse effects were found using GC-MS. GC-MS/MS allowed the quantification of nine N -nitrosamines at the low-nanogram-per-liter level.